2018
DOI: 10.1002/ange.201805050
|View full text |Cite
|
Sign up to set email alerts
|

Control of the Stereochemical Course of [4+2] Cycloaddition during trans‐Decalin Formation by Fsa2‐Family Enzymes

Abstract: Enzyme-catalyzed [4+ +2] cycloaddition has been proposed to be akey transformation process in various natural product biosynthetic pathways. Recently Fsa2 was found to be involved in stereospecific trans-decalin formation during the biosynthesis of equisetin, apotent HIV-1 integrase inhibitor.T o understand the mechanisms by which fsa2 determines the stereochemistry of reaction products,w es ought an fsa2 homologue that is involved in trans-decalin formation in the biosynthetic pathway of an enantiomerically o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(29 citation statements)
references
References 27 publications
1
28
0
Order By: Relevance
“…3 and S2 , Table S6 ). Additionally, we found that both type-I and type-II DAases can be further divided into two subclades: clade Iα functionally characterized DAase: LepI 25 ), Iβ (IccD 23 ), IIα (EqxF 31 , Fsa2 32 , Phm7 32 , and Tas3 33 ), and IIβ (CcsF 34 , CHGG_01241 35 , PoxQ 36 , and MycB 37 ). IIβ can be further divided into two groups, which reflect the two alternative functions of synthesizing either a macrocyclic (IIβ-1) or decalin (IIβ-2) ring.…”
Section: Resultsmentioning
confidence: 87%
“…3 and S2 , Table S6 ). Additionally, we found that both type-I and type-II DAases can be further divided into two subclades: clade Iα functionally characterized DAase: LepI 25 ), Iβ (IccD 23 ), IIα (EqxF 31 , Fsa2 32 , Phm7 32 , and Tas3 33 ), and IIβ (CcsF 34 , CHGG_01241 35 , PoxQ 36 , and MycB 37 ). IIβ can be further divided into two groups, which reflect the two alternative functions of synthesizing either a macrocyclic (IIβ-1) or decalin (IIβ-2) ring.…”
Section: Resultsmentioning
confidence: 87%
“…This was due to the unique identities of the respective Diels-Alderases that result from divergent evolutionary processes. Recent studies have shown that Diels-Alderase enzymes typically lose their original function and have evolved to control stereoselectivity for the cycloaddition reaction [22,[40][41][42][43][44][45][46]. Additionally, bound cofactors no longer serve a catalytic function (e.g., methyl transfer, redox), and only play a structural role in maintaining the proper active site conformation for stereochemical control [40][41][42][43][44][45][46].…”
Section: Enantioselective Diels-alderasesmentioning
confidence: 99%
“…Recent studies have shown that Diels-Alderase enzymes typically lose their original function and have evolved to control stereoselectivity for the cycloaddition reaction [22,[40][41][42][43][44][45][46]. Additionally, bound cofactors no longer serve a catalytic function (e.g., methyl transfer, redox), and only play a structural role in maintaining the proper active site conformation for stereochemical control [40][41][42][43][44][45][46]. Moreover, most Diels-Alderases have no identified catalytic residues, leading to the conclusion that these biocatalysts function by constraining the substrate in the proper orientation [40][41][42][43][44][45][46].…”
Section: Enantioselective Diels-alderasesmentioning
confidence: 99%
See 1 more Smart Citation
“…The equisetin biosynthetic pathway involves three major steps: assembly of a decalin core via the action of polyketide synthase (PKS) enzyme domains and a Diels Alderase, formation of an amino acid-derived tetramic acid moiety catalyzed by NRPS domains, and N-methylation of the tetramic acid moiety (Fig. S12) (37,39). While the domain structure of the PKS contained in the equisetin GCF remains consistent across fungi, differences in backbone enzyme amino acid sequence and the presence/absence of tailoring enzymes mediate structural variations to the scaffold.…”
Section: Usingmentioning
confidence: 99%